Development of twenty-seven genic SSR markers and screening for their association with resistance to Aeromonas hydrophila infection in rohu (Labeo rohita, Hamilton). (February 2015) - Chhotaray, Chiranjibi; Mishra, Jashobanta; Sahoo, P.K.; Das, Sweta; Mahapatra, Kanta Das; Saha, Jatindra Nath; Baranski, Matthew; Robinson, Nicholas; Das, Paramananda
Abstract: A set of 221 contigs containing simple sequence repeats (SSR) that were identified from mRNA-seq data of rohu ( Labeo rohita ) generated twenty-seven polymorphic SSRs out of which 17 had significant homology to known genes. The number of alleles per locus and observed heterozygosity ( H o ) ranged from 2 to 6 and 0.066–0.846, respectively whereas the expected heterozygosity ranged from 0.129 to 0.768. Two loci (58391f4r4 and 57246f4r4) deviated from Hardy–Weinberg Equilibrium (HWE) ( P < 0.05). Line specific allele segregation study of these markers in Aeromonas hydrophila resistant and susceptible lines of rohu revealed allelic variation in one SSR locus (58391f4r4). Expression analysis of this revealed the presence of detectable transcripts in skin, muscle, liver, intestine, kidney, spleen, brain, heart, stomach and eye tissues of rohu juveniles without showing any expression in gill tissue. It also exhibited 1.8-fold higher expression in skin tissue of resistant line over susceptible line. However, there was no significant difference noticed in its expression in muscle tissues between the lines. The contig didn't show homology to any known genes. The present study reports a putative marker linked to resistance to aeromoniasis in rohu, which could be exploited further for marker assisted breeding program. Highlights: Twenty-seven polymorphic genic SSR markers were developed from RNAseq data. One markerlocus revealed line specific allele segregation in Aeromonas hydrophila resistant and susceptible lines of rohu. This locus also exhibited 1.8-fold higher expression in skin tissue of resistant line over susceptible line.